2016
DOI: 10.1038/srep35475
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Puerarin on Rat Ventricular Myocytes and the Potential Mechanism

Abstract: Puerarin, a known isoflavone, is commonly found as a Chinese herb medicine. It is widely used in China to treat cardiac diseases such as angina, cardiac infarction and arrhythmia. However, its cardioprotective mechanism remains unclear. In this study, puerarin significantly prolonged ventricular action potential duration (APD) with a dosage dependent manner in the micromolar range on isolated rat ventricular myocytes. However, submicromolar puerarin had no effect on resting membrane potential (RMP), action pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Meanwhile, PEPs impeded acceleration of repolarization during increased heart rate (i.e., repolarization reserve), manifesting as prolonged QTc, TpTe, and TpTe/QT during stress up through 5 weeks after exposure. To prevent arrhythmia during sympathetic-induced increases in heart rate, healthy cardiomyocytes (rat and human) accelerate repolarization by enhancing the IK s current [104] via K v 7.1 phosphorylation [61]. Importantly, the long-term physiologic effects of PEPs resembled patients with concealed Long QT (LQT) Syndrome 1, who have a mutation in K v 7.1 (a major phosphorylation target of β 1 AR [61]) and prolonged QT and TpTe only during sympatho-excitation [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, PEPs impeded acceleration of repolarization during increased heart rate (i.e., repolarization reserve), manifesting as prolonged QTc, TpTe, and TpTe/QT during stress up through 5 weeks after exposure. To prevent arrhythmia during sympathetic-induced increases in heart rate, healthy cardiomyocytes (rat and human) accelerate repolarization by enhancing the IK s current [104] via K v 7.1 phosphorylation [61]. Importantly, the long-term physiologic effects of PEPs resembled patients with concealed Long QT (LQT) Syndrome 1, who have a mutation in K v 7.1 (a major phosphorylation target of β 1 AR [61]) and prolonged QT and TpTe only during sympatho-excitation [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, puerarin ameliorates nerve injury-induced depression and pain following spared nerve injury in an arginase 2-dependent manner (27). Furthermore, puerarin attenuates mechanical and chemical nerve injuries in experimental models of cerebral ischemia, diabetic complication and cardiac diseases (6,8,13). These findings indicated the antioxidative, anti-inflammatory and antiapoptotic activities of puerarin in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 85%
“…Puerarin is a phytoestrogen with potential beneficial effects in attenuating neuronal injury, diabetic kidney disease and heart failure (4-7). The herbal compound modulates oxidative stress and inflammatory responses in cardiovascular diseases (8). Furthermore, it has been reported that puerarin may be beneficial in treating diabetes mellitus (5).…”
Section: Introductionmentioning
confidence: 99%
“…Ohwi , has been wildly utilized in the treatment of cardiovascular diseases [17-18]. So far, anti-inflammatory [19], anti-oxidative [20] and anti-arrhythmia [21] effects of puerarin have been proven. Puerarin also shows acute inhibitory effects on the functional ion channels, such as Na + channels [12], inward rectified K + channels [21] and LTCC [22], in isolated CMs.…”
Section: Introductionmentioning
confidence: 99%
“…So far, anti-inflammatory [19], anti-oxidative [20] and anti-arrhythmia [21] effects of puerarin have been proven. Puerarin also shows acute inhibitory effects on the functional ion channels, such as Na + channels [12], inward rectified K + channels [21] and LTCC [22], in isolated CMs. Accumulated studies have shown that the PI3K/Akt, JAK/STAT, JNK, ERK1/2 and MAPK signaling pathways mediate the bio-effects of puerarin on various types of cells, i.e CMs [2, 17, 20], astrocytes [23], neurons [24], and retinal ganglion cells [10].…”
Section: Introductionmentioning
confidence: 99%